Multicriteria Decision-Making Methods Using Bipolar Neutrosophic Hamacher Geometric Aggregation Operators - Muhammad Jamil; Farkhanda Afzal; Deeba Afzal; Dhana Kumari Thapa; Ayesha Maqbool (Journal of Function Spaces)
The study presents a novel conception of aggregation operators (AOs) based on bipolar neutrosophic sets by using Hamacher operations and their application in modeling real-life multicriteria decision-making problems. The neutrosophic set represents incomplete, inconsistent, and indeterminate information effectively. For better understanding in this paper, we have explained all essential definitions and their respective derived neutrosophic sets (NSs) and generalization bipolar neutrosophic sets (BNSs). The primary focus of our work is Hamacher aggregation operators like BN Hamacher weighted geometric (BNHWG), BN Hamacher ordered weighted geometric (BNHOWG), and BN Hamacher hybrid geometric (BNHHG) and their required properties. The proposed scheme provides decision-makers with a comprehensive view of the complexities and vagueness in multicriteria decision-making. As compared to existing methods, these techniques provide comprehensive, increasingly exact, and precise results. Finally, we applied different types of newly introduced AOs and numerical representation on a practical example to demonstrate the effectiveness of the proposed method. Our proposed model and its application have shown improved utility and applicability in the complex decision-making process.